AC-Induced Corrosion of Cathodically Protected Pipelines: Experimental Study and Probabilistic Modeling - Yuhan Su; Emadoddin Majdabadi Farahani; Qindan Huang; Qixin Zhou (Corrosion and Materials Degradation, 2025)
This study investigated the effects of alternating current (AC) interference on pipeline steel under cathodic protection (CP). In a simulated solution, real-time electrochemical measurements and corrosion rate analysis were conducted on two steel types (C1018 and X60) under various levels of AC interference with CP. Due to the complexity of AC-induced corrosion, relying on the shift in DC potential alone cannot accurately demonstrate the corrosion behavior in the presence of AC interference. In fact, such an approach may mislead the predictions of corrosion performance. It is observed that AC interference reduced the effectiveness of CP and increased the corrosion rate of the steel, both in weight loss and Tafel Extrapolation (Tafel) measurements. The study concluded that conventional CP standards used in the field were inadequate in the presence of high AC-level interference. Furthermore, this study found that a more negative CP current density (−0.75 A/m2) could reduce the effect of AC interference by 46–93%. This is particularly shown in the case of low-level AC interference, where the reduction can reach up to 93%. Utilizing the experimental data obtained by the two measurement methods, probabilistic models to predict the corrosion rate were developed with consideration of the uncertainty in the measurements. The sensitivity analysis showed how AC interference impacts the corrosion rate for a given CP level.